Beyond Entertainment: A Systematic Review of TikTok as an Alternative Tool for Language Assessment for EFL Students - Sari, Nur Nilam; Sari, Dewi Permata; Fitriani; Kalukar, Ventje Jany; Hermagustiana, Istanti (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This systematic review evaluates TikTok‘s possible use as a modern language evaluation tool in the context of English as a Foreign Language (EFL) education. While the app remains popular as an informal learning and entertainment tool, its use as a formal evaluative instrument is largely unexplored. The review focused on 16 papers published between 2018 and 2025 and revealed patterns regarding task types, benefits, challenges, and implications associated with TikTok for language assessment. Findings show that the use of TikTok can foster engagement, motivation, and creativity and enable authentic performance assessment. However, several barriers limit the use of the platform for formal evaluation, including the short video timing, assessment rubric validity, reliability construction challenges, and restricted technological access. The review calls for educators to provide guidelines and normative instructions concerning TikTok assessments designed alongside pedagogical and technical constraints. In summary, TikTok has the potential to shift the paradigm of language assessment towards a more integrated and situated evaluation of linguistic competencies. Subsequent studies need to create specific assessment criteria regarding the effectiveness of TikTok for testing, examine the versatile skills being assessed, and assess the sustained impact of the evaluation on students’ speaking abilities.